Evaluation of maxillary sinus septa: a retrospective clinical study with cone beam computerized tomography (CBCT) - Yildirim, T. Talo; Guncu, G. -N.; Colak, M.; Nares, S.; Tozum, T. -F. (Verduci Publisher, 2017)
OBJECTIVE: To determine the prevalence, height, location, orientation, and type of maxillary sinus septa in atrophic, non-atrophic, and partially atrophic maxillary segments using cone beam computerized tomography (CBCT). PATIENTS AND METHODS: This cross-sectional study was conducted on a retrospective evaluation of CBCT images of 1000 maxillary sinus with 500 subjects from December 2009 to December 2012. The differences among gender, left and right side of maxillary sinus, type of crest and feature of septa were statistically analyzed. RESULTS: A total of 297 septa was recorded in 1000 maxillary sinuses (29.7%) with a mean height was 4.62 +/- 2.50 mm. Forty-four (8.7%) septa were located in the anterior area, 123 (24.5%) in the middle area, and 131 (26.4%) in the posterior area. Seventy maxillary sinus septa (26.1%) were observed with a mediolateral type orientation. There were no significant differences between all features of maxillary sinus septa and gender or type of crest. The only significant association identified was between type of crest and type of septa. CONCLUSIONS: The maxillary sinus septa exhibited variable characteristics according to orientation and type of crest. CBCT analysis is very important and should be performed before maxillary sinus surgery to prevent possible complications.
Keywords: Tomography; Sinus; Anatomy; Radiology; Humans